Repressing phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit gamma by microRNA-142-3p restrains the progression of hepatocellular carcinoma. Issue 1 (1st January 2022) - Zeng, Chuanli; Yuan, Gang; Hu, Yaoren; Wang, Donghui; Shi, Xiaojun; Zhu, Dedong; Hu, Airong; Meng, Yina; Lu, Jialin
ABSTRACT: This paper probes the mechanisms underlying miR-142-3p's modulation of hepatocellular carcinoma (HCC) invasion and apoptosis. Quantitative real-time PCR and Western blot monitored the miR-142-3p profile in HCC tissues and non-tumor tissues. The correlation between miR-142-3p expression and HCC patients' clinicopathological indicators was analyzed. miR-142-3p overexpression and knockdown models were established in HCC cell lines. Cell proliferation was gauged by the colony formation assay and BrdU staining. For measuring apoptosis, flow cytometry and Western blot were implemented. Transwell assay tested cell migration and invasion. miR-142-3p mimics or inhibitors were transfected in Huh7 and HCCLM3 cells. The targeting association between miR-142-3p and PIK3CG was predicted through bioinformatics and further verified by related experiments. The influence of PIK3CG overexpression on miR-142-3p's role in HCC was assayed. A xenografted tumor model was built in mice to validate miR-142-3p knockdown's influence on HCC in vivo . As a result, miR-142-3p exhibited a decreased profile in HCC tissues and cells. Overexpressing miR-142-3p accelerated apoptosis and suppressed the PI3K/AKT/HIF-1α signal. Knocking down miR-142-3p presented opposite effects. PIK3CG overexpression dampened the anti-tumor effect of miR-142-3p. miR-142-3p repressed HCC invasion and intensified apoptosis to restrain HCC by abating the PIK3CG-mediated PI3K/AKT/HIF-1α pathway.